1986
DOI: 10.1161/01.atv.6.6.664
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle phenotypic expression in human carotid arteries. II. Atherosclerosis-free diffuse intimal thickenings compared with the media.

Abstract: The volume fraction of synthetic organelles in smooth muscle cells from areas of atherosclerosis-free, diffuse intimal thickenings (DIT) and media of human carotid artery has been determined morphometrically. Tissue was obtained at autopsy from men and women aged 35 to 80 years, at 6 to 12 hours after death. With both sexes, the volume fraction of synthetic organelles in smooth muscle cells from the DIT was not significantly different from the volume fraction of synthetic organelles in cells of the subjacent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
93
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 0 publications
6
93
0
2
Order By: Relevance
“…VSMCs displaying the synthetic phenotype are characterized by increased numbers of synthetic organelles such as lysosomes, Golgi, mitochondria, and endoplasmic reticulum, by which proteases are extensively produced. 7,8 These findings and our results suggest that increases in cathepsin D and ACE are associated with the increases in intracellular organelles that occur with the change to the synthetic phenotype and that the increases in cathepsin D and ACE generate Ang II.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…VSMCs displaying the synthetic phenotype are characterized by increased numbers of synthetic organelles such as lysosomes, Golgi, mitochondria, and endoplasmic reticulum, by which proteases are extensively produced. 7,8 These findings and our results suggest that increases in cathepsin D and ACE are associated with the increases in intracellular organelles that occur with the change to the synthetic phenotype and that the increases in cathepsin D and ACE generate Ang II.…”
Section: Discussionsupporting
confidence: 59%
“…After several passages, VSMCs dedifferentiate and display the synthetic phenotype, which is characterized by a reduction in the volume fraction of myofilaments and an increase in synthetic organelles such as the Golgi, mitochondria, and endoplasmic reticulum, by which proteases, growth factors, and cytokines are extensively produced. 7,8 It is possible, therefore, that the mechanism underlying Ang II generation in homogeneous cultures of VSMCs is associated with the change from the contractile to the synthetic phenotype.…”
mentioning
confidence: 99%
“…There was an increase of 318% in the cytoplasmic volume occupied by synthetic organelles of SMCs in areas of DIT, when compared to medial SMCs. Mosse et al (1985), studying human carotids with atherosclerosis, reported a twofold increase in the concentration of organelles of intimal SMCs and a great variability in the content of organelles of these cells when compared to medial SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…SMCs at the more synthetic end of the phenotype spectrum are assumed to be responsible for ECM synthesis in both the media and intima [25]. Of interest, several studies showed that SMCs located in both intimal thickenings and advanced atherosclerotic lesions display more synthetic features, suggesting that also in atherosclerosis synthetic SMC are responsible for ECM synthesis [25][26][27]. In analogy to the myocardium, the vascular wall also contains fibroblasts, located mainly in the adventitia.…”
Section: S Heeneman Et Almentioning
confidence: 99%